1991
DOI: 10.1210/mend-5-4-521
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the a Inhibin Gene by Cyclic Adenosine 3′,5′-Monophosphate after Transfection into Rat Granulosa Cells

Abstract: Inhibin gene expression in the ovary is stimulated by FSH, which uses cAMP as an intracellular second messenger. To examine further the transcriptional regulation of the alpha inhibin gene by FSH and cAMP, we have isolated and characterized a genomic clone that contains the entire rat alpha inhibin gene. Sequence analysis of the alpha inhibin promoter region revealed several potential cAMP response elements (CREs) and transcription factor AP2-binding sites that might mediate cAMP regulation. To determine the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
60
0
3

Year Published

1993
1993
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(68 citation statements)
references
References 54 publications
5
60
0
3
Order By: Relevance
“…In Inha/Tag mice, LH stimulation is likely to increase the cAMP levels of target cells and also to stimulate the inhibin-a promoter, leading to increased T-antigen expression. It has been shown that an important component of gonadotropin-regulated, cAMP-dependent, inhibin-a-subunit gene expression is the synthesis or activation of cAMP response element (CRE) binding protein (CREB) (Pei et al, 1991). Both gonadotropins can induce the phosphorylation of CREB, leading to its activation (Mukherjee et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…In Inha/Tag mice, LH stimulation is likely to increase the cAMP levels of target cells and also to stimulate the inhibin-a promoter, leading to increased T-antigen expression. It has been shown that an important component of gonadotropin-regulated, cAMP-dependent, inhibin-a-subunit gene expression is the synthesis or activation of cAMP response element (CRE) binding protein (CREB) (Pei et al, 1991). Both gonadotropins can induce the phosphorylation of CREB, leading to its activation (Mukherjee et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the genes of another protein family within the TGF-p superfamily have been found to be regulated differently, in that the promoters of TGF-P1 and TGF-/X2 were found to be regulated by Spl, whereas that of TGF-p3 was not (Geiser et al, 1993). S1 -nuclease-protection studies and primer-extension analyses have identified the transcriptional start sites of the rat (Feng et al, 1989;Albiston et al, 1990;Pei et al, 1991) and mouse (Su and Hsueh, 1992) a-inhibin genes to occur at -73 to -75 bp and at -71 bp, respectively, relative to the translational start site. The present study identified the start site of the bovine gene to be at position -82 (G; Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Signalling mechanisms operating through the PKA and PKC pathways have been suggested to play roles in the regulation of inhibidactivin gene expression (Klaij et al, 1990(Klaij et al, , 1992Pei et al, 1991 ;Tanimoto et al, 1992;Tanimoto et al, 1993;Najmabadi et al, 1993a,b). As indicated in Figs 1-3, two predicted CRE sites are found following searches of the sequence data using SIGNAL SCAN/TFD, one each occurring in the a-and P,-inhibidactivin 5'-flanking regions.…”
Section: Dnase I Footprintingmentioning
confidence: 99%
See 2 more Smart Citations